Ensuring quality assurance of the teaching-learning process in African univeristies (2012)
Higher education is at the crossroads in most African countries. At one end there is high demand for access to higher education and at the other the skills acquired is questioned. In other to survive in the competive world of globalization, all higher education institutions should therefore engage in extensive review of literature on diverse views of quality assurance, quality control and total assurance practices in some advanced and African countries. It answered the question of how quality of the teaching learning process can be assessed and how to enhance the appropriate skills in our university graduates. The paper recommended that greater emphasis should be placed on the supervision and monitoring of the teaching-learning process, so that university graduates will acquires the appropraite skills required by the society.